Proceedings of the Annual Conference of Indonesian Association for Public Administration (IAPA 2019) 2020
DOI: 10.2991/aebmr.k.200301.013
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Reduction and Financial Literacy for Women in Indonesia

Abstract: This article aims to discuss financial literacy as an integral part of poverty alleviation programs through women's economic participation. Financial literacy is a supporter in increasing economic participation. Financial literacy is a set of information that refers to an individual's ability to effectively assess and decide the use and management of money. The method used in this study is a literature review of several articles related to the research topic as well as other report documents and relevant case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Research has demonstrated that financial literacy influences household behavior, investment decisions, and poverty reduction across different regions and demographics(Setyorini et al, 2021;Hussain et al, 2022;Wardhono & Nasir, 2022). Additionally, financial literacy has been identified as a key factor in improving financial inclusion and reducing poverty, particularly for women and youth(Arini et al, 2020;Zhu & Chou, 2018).…”
mentioning
confidence: 99%
“…Research has demonstrated that financial literacy influences household behavior, investment decisions, and poverty reduction across different regions and demographics(Setyorini et al, 2021;Hussain et al, 2022;Wardhono & Nasir, 2022). Additionally, financial literacy has been identified as a key factor in improving financial inclusion and reducing poverty, particularly for women and youth(Arini et al, 2020;Zhu & Chou, 2018).…”
mentioning
confidence: 99%